"Understanding restaurant firms" debt-equity financing. Issue 12 (11th December 2017) - Mun, Sung Gyun; Jang, SooCheong (Shawn)
Abstract : Purpose: The purpose of this study was to extend the understanding of restaurant firms' overall debt and equity financing practices by considering what drives equity financing. More importantly, this study attempted to identify whether an optimal financial leverage point exists in the relationship between debt financing and equity financing for restaurant firms. Design/methodology/approach: This study used fixed-effects regression models with a sample of 1, 549 unbalanced firm-year panel data to identify restaurant firms' financial practices and the impacts of financial constraints. Findings: First, restaurant firms tend to issue long-term debt to pay back existing debt. However, the amount of debt does not exactly match the debt's maturity. Second, small restaurant firms' net debt financing, as well as net equity financing, has an inverted-U-shaped relationship with financial leverage. Finally, the effect of financial leverage on external financing significantly differs between small and large restaurant firms. Practical implications: Restaurant firms routinely use both debt and equity financing interchangeably to manage their financial constraints and target debt ratio. Further, firm size is an important indicator of financial constraints, while equity financing plays an important role in managing an optimal target debt ratio. Originality/value: This study is unique in that it considers determinants of restaurant firms' long-term debt financing as well as equity financing. This study also examines differences in long-term debt and equity financing practices between financially constrained and unconstrained firms.